Impact of monetary policy uncertainty on Asian exchange rates. - Park, Donghyun (Metro Manila, Philippines Asian Development Bank, 2019)
Exchange rate levels and fluctuations are key economic variables that affect international trade and investment. The analysis reveals that monetary policy uncertainty in the United States tends to increase the variance of exchange rates in some Asian countries, but has no systematic effect on exchange rate levels. Data show that heightened uncertainty about monetary policy in the United States can contribute to exchange rate volatility in Asian countries.
Keywords: Public administration; Monetary policy; Uncertainty; Electronic books